2022
DOI: 10.3390/nu14122519
|View full text |Cite
|
Sign up to set email alerts
|

An Exploration of How Solar Radiation Affects the Seasonal Variation of Human Mortality Rates and the Seasonal Variation in Some Other Common Disorders

Abstract: Many diseases have large seasonal variations in which winter overall mortality rates are about 25% higher than in summer in mid-latitude countries, with cardiovascular diseases and respiratory infections and conditions accounting for most of the variation. Cancers, by contrast, do not usually have pronounced seasonal variations in incidence or mortality rates. This narrative review examines the epidemiological evidence for seasonal variations in blood pressure, cardiovascular disease rates and respiratory vira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 156 publications
1
14
0
Order By: Relevance
“…The incidence and mortality rates for cardiovascular and respiratory diseases are much higher in winter than in summer. As a result, all-cause mortality rates in winter are 25% higher than in summer in the U.S. [ 22 , 23 ]. Since the risk for cardiovascular disease and infectious diseases is inversely correlated with serum 25(OH)D concentrations, it would be very useful to understand why the concentrations change with season and how to maintain summertime concentrations in winter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence and mortality rates for cardiovascular and respiratory diseases are much higher in winter than in summer. As a result, all-cause mortality rates in winter are 25% higher than in summer in the U.S. [ 22 , 23 ]. Since the risk for cardiovascular disease and infectious diseases is inversely correlated with serum 25(OH)D concentrations, it would be very useful to understand why the concentrations change with season and how to maintain summertime concentrations in winter.…”
Section: Discussionmentioning
confidence: 99%
“…A vitamin D supplementation study reported that for 400, 4000, or 10,000 IU/day vitamin D 3 for 6 months, 162, 320, and 1289 genes were up- or down-regulated in their white blood cells, respectively [ 32 ]. This finding suggests that the increased risk of cardiovascular disease and mortality rates in winter is largely due to lower 25(OH)D concentrations in winter [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The authors had no explanation for their findings. However, a report in 2022 showed that seasonal changes in serum 25(OH)D concentrations had the highest impact on seasonal variations in mortality rates, with seasonal changes in temperature having a similar but lesser effect [ 75 ].…”
Section: Cardiovascular Diseasementioning
confidence: 99%
“…Additional support for the protective role of vitamin D supplementation comes from the fact that CVD mortality rates are about 25% higher in winter than those in summer as discussed in a recent review of the factors affecting the seasonality of CVD incidence and CVD mortality rates 10 where seasonal changes in temperature and serum 25(OH)D concentrations and elevated parathyroid hormone concentrations were discussed in detail. While the evidence regarding temperature is strong, so is that for vitamin D, and which is more important in particular situations may depend on how much exposure there is to cold temperatures or to extreme heat.…”
mentioning
confidence: 99%